Electric vacuum ceramic-metallization cold spraying glaze and production method thereof
Through the electrovacuum ceramic-metalized cold glaze spraying process, the glaze of specific formulas and simplified production methods are used to solve the problems of uneven glaze layer thickness and many defects in the glaze spraying process of the electrovacuum ceramic shell, and the glaze layer is realized Uniform, dense and high quality, reducing production costs and energy consumption.
Patent Information
- Application Number
- CN202411706716.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
AI Technical Summary
现有电真空陶瓷壳喷釉工艺存在釉层厚度不均、橘皮釉、堆釉等缺陷,且热喷釉需要高温加热,耗电且工人劳动强度大,冷喷釉在低吸水率和光洁表面下难以粘附,导致釉层不均匀。
Using the electrovacuum ceramic-metalized cold-spraying process, a simplified production method (including components such as potassium feldspar, firing talc, calcite, clay, quartz, barium carbonate, zirconium dioxide, etc.) and a simplified production method (including Ball milling, iron removal, sieving, vacuum defoaming, modulation and stirring) to achieve uniform, dense and high quality of the glaze layer.
The uniformity, density and gloss of the glaze layer are achieved, impurities and defects are reduced, glaze hardness and emulsion are improved, production costs are reduced, and energy consumption is saved.
Smart Images

Figure BDA0005154687170000041 
Figure BDA0005154687170000042 
Figure BDA0005154687170000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric vacuum ceramic metallized glaze spraying, in particular to an electric vacuum ceramic-metallized cold glaze spraying and a production method thereof. Background Art
[0002] The electric vacuum ceramic shell is a key structural component of the vacuum arc chamber. The electric vacuum ceramic shell is an insulating shell, which forms an airtight insulation system with the moving end cover, the static end cover, the bellows, etc. In order to ensure that the ceramic shell has good insulation, electrical resistance and corrosion resistance, the electric vacuum ceramic shell is generally made of high-aluminum porcelain (A-95 porcelain), which has a high sintering temperature, a dense structure, and an extremely low porosity, and has a very weak ability to absorb water. In addition, the size requirements of the electric vacuum ceramic shell are high. The ceramic shell needs to be machined to ensure the dimensional accuracy of the ceramic shell, and then it can be glazed after cleaning and drying. When glazing, according to the design requirements, the outer surface of the ceramic shell needs a continuous and dense glaze layer, and no glaze is allowed to adhere to the inner surface and the outer surface of the two ends of the ceramic shell within 1.5 to 2mm (commonly known as the glaze line). The glaze line width is too narrow. During the metallization sintering process, the glaze disperses, and the glass phase in the glaze layer penetrates into the metallization layer in large quantities, which seriously affects the quality of the metallization layer on both ends. For the assembly workshop of vacuum interrupter, the narrower the glaze line, the better. When the glaze line is too wide, the glaze line area is easy to absorb dirt during vacuum brazing, which increases the difficulty of subsequent processing. The thickness of the glaze layer of the ceramic adsorption effect is required to be uniform (depending on the thickness of different products, it is generally required to be within 80-300μm), the deviation of the glaze amount of the same product shall not exceed 10%, and impurities, glaze deficiency, glaze accumulation, orange peel glaze and other defects are not allowed on the surface of the glaze layer. These defects cause a significant increase in production costs. At the same time, all glaze layers of the electric vacuum ceramic shell need to have good insulation, high temperature viscosity, corrosion resistance and wear resistance.
[0003] The existing electric vacuum ceramic shell glaze spraying process basically adopts hot glaze spraying. After the sprayed glaze slurry contacts the heated ceramic shell, the water evaporates rapidly, and the glaze particles adhere to the outer surface of the ceramic shell. The disadvantages of hot glaze spraying process: ① Due to the different temperatures of the ceramic shell, it causes defects such as orange peel glaze, glaze heaping, wrinkling, and uneven glaze layer thickness; ② It consumes electric energy when heating; ③ It takes time and effort to put the ceramic shell in and out of the oven, which increases the labor intensity of workers; ④ It is easy to scald employees after the ceramic shell is heated; ⑤ The heating of the ceramic shell affects the ambient temperature of the workplace, which is very uncomfortable for employees in summer. Cold glaze spraying is mainly used on porcelain used in daily life. For electric vacuum ceramic shells, the cold glaze spraying process is because the surface of the electric vacuum ceramic shell is smooth (roughness Ra is 0.8~1.6μm) and the water absorption rate is low (<0.3%). When spraying glaze at room temperature, the water evaporates slowly, and it is not easy to adhere to the glaze slurry. It is easy to cause glaze dripping and uneven glaze layer. Summary of the invention
[0004] The purpose of the present invention is to provide an electric vacuum ceramic-metallized cold spray glaze and a production method thereof. The cold spray glaze process is implemented on the surface of the sintered electric vacuum ceramic shell, and the glaze layer has uniform thickness, compactness, good glossiness and a certain opacity.
[0005] The technical solution of the present invention is: an electric vacuum ceramic-metallized cold spray glaze, which comprises the following components by weight: potassium feldspar: 55-75 parts, burned talc: 0.5-5 parts, calcite: 0.1-2 parts, clay: 10-20 parts, quartz: 10-20 parts, barium carbonate: 0-5 parts, and zirconium dioxide: 0-5 parts.
[0006] The invention comprises the following components: potassium feldspar: 60-70 parts, calcined talc: 1.5-4 parts, calcite: 0.5-1.5 parts, clay: 13-17 parts, quartz: 12-18 parts, barium carbonate: 1-4 parts, and zirconium dioxide: 1-4 parts.
[0007] Potassium feldspar: 63-67 parts, burned talc: 2.5-3 parts, calcite: 0.8-1.2 parts, clay: 14-16 parts, quartz: 14-16 parts, barium carbonate: 2.4-2.6 parts, zirconium dioxide: 2.2-2.6 parts.
[0008] It also includes 0.1 to 0.2 parts of water reducing agent and 0.01 to 0.05 parts of defoaming agent.
[0009] The water reducing agent is triamine citrate, and the defoaming agent is polyether polyol.
[0010] The production method of electric vacuum ceramic-metallized cold spray glaze has the following specific steps:
[0011] S1 Material weighing
[0012] Weigh the powders of various raw materials and put them into a batching barrel, add water according to the weight ratio of powder: water = 1:0.6-0.9, mix to obtain glaze slurry, and add the glaze slurry into the vertical ball mill by a vacuum feeder;
[0013] S2 ball mill
[0014] Start the vertical ball mill to ball-mill the glaze slurry, and stop automatically after 60 to 120 minutes of ball milling;
[0015] S3 Iron Removal
[0016] The glaze slurry is deironed by the deironing system, and the deironing time is 90 to 150 minutes. After the deironing is completed, the glaze slurry is placed in a bucket for standby use;
[0017] S4 Screening
[0018] Release the spare glaze slurry and pass it through a 200-mesh sieve;
[0019] S5 Vacuum Defoaming
[0020] The sieved glaze slurry is injected into a vacuum mixer to perform vacuum defoaming on the glaze slurry;
[0021] S6 glaze slurry preparation
[0022] Add water reducing agent and defoaming agent to the vacuum defoamed glaze slurry;
[0023] S7 glaze slurry mixing
[0024] Put the prepared glaze slurry into the pressure tank and turn on the stirring device to prevent the glaze from settling.
[0025] Beneficial effects of the present invention: The cold spray glaze formula and process of the present invention are simple in process, and the prepared glaze slurry has strong thixotropy and suitable fluidity. Since the glaze slurry has suitable fluidity and strong adhesion, the glaze slurry does not flow when it is naturally dried on the surface of the ceramic shell, and can be well attached to the surface of the ceramic shell. After high-temperature sintering in a hydrogen environment, a smooth, bright, uniform, dense glaze surface with a certain opacity can be obtained, and impurities in the glaze layer can be effectively controlled.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] ① The formula and preparation process of the glaze are simple. The raw materials for the glaze are all traditional glaze materials, which are economical and applicable. There is no need to prepare a special suspending agent in the glaze, and the characteristics of the plastic materials potassium feldspar and clay are fully utilized. No organic binder is required to be added to the glaze slurry, so as to avoid insufficient oxidation of organic matter during glaze firing, carbon residue on the ceramic shell and glaze layer, and black glaze and porcelain flowers during metallization sintering.
[0028] ② In view of the characteristics of electric vacuum ceramics, such as dense structure, extremely low porosity and weak water adsorption capacity, through the glaze ratio, only a small amount of water reducer (triammine citrate) needs to be introduced to control the moisture content of the glaze slurry within an appropriate range. The glaze slurry has the fluidity suitable for cold spraying glaze, and the obtained glaze layer has uniform and dense thickness.
[0029] ③ The glaze of the present invention obtains suitable high-temperature viscosity by adjusting the formula, which effectively controls the dispersion of the glaze layer during metallization sintering, avoids the glass phase in the glaze layer from penetrating into the metallization layer and affecting the quality of the metallization layer. By utilizing this property, the glaze line can be controlled to about 0.5 mm.
[0030] ④ The glaze of the present invention can obtain a wider sintering temperature range by adjusting the formula. After the glaze spraying is completed, half glaze is fired (half glaze temperature is 1100-1250°C, full glaze temperature is 1400-1500°C), which saves energy consumption.
[0031] ⑤ Vacuum defoam the glaze slurry and add defoaming agent to remove the bubbles in the glaze slurry.
[0032] ⑥ The glaze spraying feeding system adopts pressure tank for feeding. The constant pressure ensures the stability of feeding, improves the consistency of glaze layer thickness, and the deviation of spraying glaze weight does not exceed 5%.
[0033] The applicant conducted a comparative test before and after the cold spray glaze was applied, and the results are shown in Table 1.
[0034] Table 1 Comparative test results before and after cold spray glaze implementation
[0035]
[0036] Test summary: The applicant has conducted a large number of tests on the effect of cold spray glaze. Some data are shown in the table above. The production effect obtained through the above experimental results shows that after the implementation of cold spray glaze, there are obvious improvements in glaze defects, glaze accumulation, impurities, glaze scratches, etc., especially the glaze defects of the corrugated ceramic shell have been significantly improved. Due to the emulsification effect of the glaze, the proportion of impurities has been reduced. After the hardness of the glaze is improved, the proportion of glaze scratches has been reduced.
[0037] The applicant further conducted a large number of tests on the effects of the cold spray glaze formulation. The specific components and results are shown in Tables 2 and 3 below:
[0038] Table 2 Cold spray glaze formula component test
[0039]
[0040] Table 3 Summary of cold spray glaze formulation components
[0041]
[0042] Test summary: The applicant has conducted a large number of tests on the effect of cold spray glaze formula. Some data are selected in Tables 2 and 3 above. The production effect obtained through the above experimental results shows that potassium feldspar brings in auxiliary solvents such as alkali metal oxides K2O, Na2O and necessary Al2O3 and SiO2, which can reduce the sintering temperature of the glaze, increase the fluidity of the molten glaze, and at the same time increase the refractive index and brightness of the glaze layer. When excessive K2O is added, the viscosity of the glaze in the high-temperature molten state is increased, and the fluidity of the high-temperature molten state is reduced, which is very beneficial for glaze line control. However, with the increase of the viscosity of the high-temperature molten state, orange peel glaze is easy to be produced and the gas is not easy to be discharged, which is easy to cause closed pores and affect the quality of the glaze surface. The main components of clay are Al2O3 and SiO2. SiO2 is the main component of glaze, which can increase the melting temperature and viscosity of some, give the glaze high mechanical strength (such as hardness and wear resistance), improve the whiteness, transparency, chemical stability of the glaze and reduce the thermal expansion coefficient of the glaze. Al2O3 is a network intermediate for forming glaze. It can combine with SiO2 and alkali metal oxides to improve the performance of glaze. With the increase of Al2O3 content, the hardness of glaze surface is significantly improved. The gloss of glaze surface can be controlled by adjusting the molar ratio of Al2O3 / SiO2. Clay can significantly improve the suspension and stability of glaze slurry, thereby ensuring the uniformity and stability of glaze slurry. Because clay has good plasticity, it can improve the adhesion of glaze, so that glaze can be more evenly attached to the surface of ceramic shell. Excessive use can easily cause the viscosity of glaze slurry to be too high, which is not conducive to spraying. With the increase of clay dosage, the viscosity of slurry increases, which has a greater impact on the iron removal effect of glaze slurry and increases the impurity content. The main components of talc are SiO2 and MgO. The purpose of adding talc to glaze is to introduce an appropriate amount of magnesium oxide. MgO is a strong active cosolvent, which can improve the fluidity of glaze melt and promote the formation of the intermediate layer between body and glaze, and reduce the cracking of glaze surface. MgO also has a certain opacity in glaze, and has a good opacity effect when combined with zirconium dioxide. Excessive introduction of zirconium dioxide will cause the glaze temperature to increase. Barium carbonate decomposes into BaO at high temperature. Proper addition of BaO in the glaze can significantly improve the gloss and refractive index of the glaze, making the glaze smoother and more delicate. BaO is also a strong co-solvent in the glaze. Excessive addition will reduce the temperature of the glaze. Potassium feldspar and clay are both good plastic materials. With the increase of their content, the content of K2O and Na2O alkali metal oxides in the glaze increases, the sintering temperature of the glaze is reduced, and the sintering temperature range is widened. There are obvious improvements in glaze deficiency, glaze accumulation, impurities, glaze scratches, etc., especially the glaze deficiency of the corrugated ceramic shell has been significantly improved. Due to the emulsification effect of the glaze, the proportion of impurities is reduced. After the hardness of the glaze is improved, the proportion of glaze scratches is reduced. The role of the water reducer is to reduce the water content of the glaze slurry and adjust the fluidity of the glaze slurry. If the water content in the glaze slurry is too high, it is very easy to flow when spraying the glaze, and the glaze cannot be sprayed.By reducing the water content in the glaze slurry, the glaze is prevented from flowing. As the water content decreases, the fluidity of the glaze slurry can only be adjusted by adding a water reducing agent, thereby enhancing the atomization effect of the glaze slurry. The present invention realizes the cold spraying glaze process on the electric vacuum ceramic by organically combining the various raw materials in the formula. The obtained glaze has good gloss, no opacity, no orange peel glaze, and the glaze hardness is 7 to 8 levels. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0044] Example 1. An electric vacuum ceramic-metallized cold spray glaze comprises the following components by weight: potassium feldspar: 55-75 parts, calcite: 0.5-5 parts, calcite: 0.1-2 parts, clay: 10-20 parts, quartz: 10-20 parts, barium carbonate: 0-5 parts, and zirconium dioxide: 0-5 parts.
[0045] It also includes 0.1 to 0.2 parts of water reducing agent and 0.01 to 0.05 parts of defoaming agent.
[0046] The water reducing agent is triamine citrate, and the defoaming agent is polyether polyol.
[0047] The production method of electric vacuum ceramic-metallized cold spray glaze has the following specific steps:
[0048] S1 Material weighing
[0049] Weigh the powders of various raw materials and put them into a batching barrel, add water according to the weight ratio of powder: water = 1:0.6-0.9, mix to obtain glaze slurry, and add the glaze slurry into the vertical ball mill by a vacuum feeder;
[0050] S2 ball mill
[0051] Start the vertical ball mill to ball-mill the glaze slurry, and stop automatically after 60 to 120 minutes of ball milling;
[0052] S3 Iron Removal
[0053] The glaze slurry is deironed by the deironing system, and the deironing time is 90 to 150 minutes. After the deironing is completed, the glaze slurry is placed in a bucket for standby use;
[0054] S4 Screening
[0055] Release the spare glaze slurry and pass it through a 200-mesh sieve;
[0056] S5 Vacuum Defoaming
[0057] The sieved glaze slurry is injected into a vacuum mixer to perform vacuum defoaming on the glaze slurry;
[0058] S6 glaze slurry preparation
[0059] Add water reducing agent and defoaming agent to the vacuum defoamed glaze slurry;
[0060] S7 glaze slurry mixing
[0061] Put the prepared glaze slurry into the pressure tank and turn on the stirring device to prevent the glaze from settling.
[0062] When spraying glaze, the ceramic shell rotates at a fixed speed, and the spray gun reciprocates at a constant speed at a certain angle (different tube types have different angles). After the glaze slurry is atomized, it is sprayed on the outer surface of the ceramic shell. The spray gun angle changes automatically when the spray gun changes direction to ensure the uniformity of the glaze layer at the crests and troughs of the corrugated ceramic. The glaze spraying feeding system uses a pressure tank for feeding. The constant pressure ensures the stability of the feeding, improves the consistency of the glaze layer thickness, and the deviation of the spray glaze weight does not exceed 5%. By adjusting the high-temperature viscosity of the glaze, the glaze line width is controlled at about 0.5mm without affecting the quality of the metallized layer, and a special fixture is used to achieve this, so there is no glaze in the glaze line area. The glaze supply and glaze spraying process are as follows:
[0063] (1) Setting glaze spraying parameters
[0064] Spray glaze machine speed: 100 rpm
[0065] Spray gun angle: -30°~+30°
[0066] Spray gun pressure: 0.4~0.6MPa
[0067] Feed pressure: 0.5~2bar
[0068] Atomization state adjustment: in line with process requirements.
[0069] (2) First test spraying
[0070] Each tube type needs to be tested before spraying glaze, and the number of spraying times is determined based on the test results. The operation process is as follows:
[0071] 1) Clamping
[0072] Install the lower fixture on the turntable of the glaze spraying machine, place the ceramic shell on the annular groove of the lower fixture, then install the middle fixture, and then place another ceramic shell, and finally cover the upper fixture to complete the clamping (Note: only place one ceramic shell with a length greater than 160mm).
[0073] 2) Turn on the start button of the automatic glaze spraying machine to automatically spray the glaze, and perform test spraying according to the preset number of spraying times.
[0074] 3) Glaze thickness detection
[0075] The thickness detection of glaze layer is realized by controlling the weight of glaze spraying. The ceramic shell to be sprayed with glaze is weighed, and then weighed again after spraying the glaze to calculate the weight of the glaze. The number of times of glazing is determined according to the designed weight of the glaze.
[0076] Example 2
[0077] An electric vacuum ceramic-metallized cold spray glaze comprises the following components by weight: potassium feldspar: 60-70 parts, calcined talc: 1.5-4 parts, calcite: 0.5-1.5 parts, clay: 13-17 parts, quartz: 12-18 parts, barium carbonate: 1-4 parts, and zirconium dioxide: 1-4 parts.
[0078] Example 3
[0079] An electric vacuum ceramic-metallized cold spray glaze comprises the following components by weight: potassium feldspar: 63-67 parts, calcite: 2.5-3 parts, calcite: 0.8-1.2 parts, clay: 14-16 parts, quartz: 14-16 parts, barium carbonate: 2.4-2.6 parts, and zirconium dioxide: 2.2-2.6 parts.
[0080] Example 4
[0081] An electric vacuum ceramic-metallized cold spray glaze comprises the following components by weight: 64 parts of potassium feldspar, 2.8 parts of calcite, 0.7 parts of calcite, 14 parts of clay, 13 parts of quartz, 1.8 parts of barium carbonate, 3.7 parts of zirconium dioxide and 80 parts of pure water. All the materials and pure water are added into a ball mill to prepare glaze slurry, and then 0.1 parts of a water reducing agent and 0.01 parts of a defoaming agent are added to prepare the cold spray glaze slurry.
[0082] Example 5
[0083] An electric vacuum ceramic-metallized cold spray glaze comprises the following components by weight: potassium feldspar: 72 parts, calcined talc: 4 parts, calcite: 1 part, clay: 9 parts, quartz: 8.2 parts, barium carbonate: 4 parts, zirconium dioxide: 1.8 parts, and pure water: 85 parts. All the materials and pure water are added into a ball mill to prepare glaze slurry, and then 0.2 parts of a water reducing agent and 0.02 parts of a defoaming agent are added to prepare the cold spray glaze slurry.
Claims
1. An electric vacuum ceramic-metallized cold spray glaze, characterized in that: The invention comprises the following components by weight: potassium feldspar: 55-75 parts, calcined talc: 0.5-5 parts, calcite: 0.1-2 parts, clay: 10-20 parts, quartz: 10-20 parts, barium carbonate: 0-5 parts, and zirconium dioxide: 0-5 parts.
2. The electric vacuum ceramic-metallized cold spray glaze according to claim 1, characterized in that: The invention comprises the following components: potassium feldspar: 60-70 parts, calcined talc: 1.5-4 parts, calcite: 0.5-1.5 parts, clay: 13-17 parts, quartz: 12-18 parts, barium carbonate: 1-4 parts, and zirconium dioxide: 1-4 parts.
3. The electric vacuum ceramic-metallized cold spray glaze according to claim 2, characterized in that: Potassium feldspar: 63-67 parts, burned talc: 2.5-3 parts, calcite: 0.8-1.2 parts, clay: 14-16 parts, quartz: 14-16 parts, barium carbonate: 2.4-2.6 parts, zirconium dioxide: 2.2-2.6 parts.
4. The electric vacuum ceramic-metallized cold spray glaze according to any one of claims 1 to 3, characterized in that: The ratio of the water reducing agent to the powder is 1 to 5:1000, and the ratio of the defoaming agent to the powder is 1 to 5:10000.
5. The electric vacuum ceramic-metallized cold spray glaze according to claim 4, characterized in that: The water reducing agent is triamine citrate, and the defoaming agent is polyether polyol.
6. The method for producing electric vacuum ceramic-metallized cold spray glaze according to any one of claims 1 to 5, characterized in that: The specific steps are as follows: S1 Material weighing Weigh the powders of various raw materials and put them into a batching barrel, add water according to the weight ratio of powder: water = 1:0.6-0.9, mix to obtain glaze slurry, and add the glaze slurry into the vertical ball mill by a vacuum feeder; S2 ball mill Start the vertical ball mill to ball-mill the glaze slurry, and stop automatically after 60 to 120 minutes of ball milling; S3 Iron Removal The glaze slurry is deironed by the deironing system, and the deironing time is 90 to 150 minutes. After the deironing is completed, the glaze slurry is placed in a bucket for standby use; S4 Screening Release the spare glaze slurry and pass it through a 200-mesh sieve; S5 Vacuum Defoaming The sieved glaze slurry is injected into a vacuum mixer to perform vacuum defoaming on the glaze slurry; S6 glaze slurry preparation Add water reducing agent and defoaming agent to the vacuum defoamed glaze slurry; S7 glaze slurry mixing Put the prepared glaze slurry into the pressure tank and turn on the stirring device to prevent the glaze from settling.